2020
DOI: 10.1098/rsos.200458
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and preference in isolation: a test of their different influences on responses to self-isolation during the COVID-19 outbreak

Abstract: This multi-wave study examined the extent that both preference and motivation for time alone shapes ill-being during self-isolation. Individuals in the USA and the UK are self-isolating in response to the COVID-19 outbreak. Different motivations may drive their self-isolation: some might see value in it (understood as the identified form of autonomous motivation), while others might feel forced into it by authorities or close others (family, friends, neighbourhoods, doctors; the external form of controlled mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
6
26
0
Order By: Relevance
“…With respect to well-being and mental health indicators, the results favour the direction of change which reflects that this sample of individuals from Wuhan, China, have coped adaptively and remained psychologically stable, if not improved, after lockdown was lifted. Consistent with other longitudinal data in the UK and US showing the stability of mental health and well-being over time during lockdown [3,35], our results suggest that for our participants life after lockdown may have settled into the 'new normal'.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…With respect to well-being and mental health indicators, the results favour the direction of change which reflects that this sample of individuals from Wuhan, China, have coped adaptively and remained psychologically stable, if not improved, after lockdown was lifted. Consistent with other longitudinal data in the UK and US showing the stability of mental health and well-being over time during lockdown [3,35], our results suggest that for our participants life after lockdown may have settled into the 'new normal'.…”
Section: Resultssupporting
confidence: 91%
“…Some emerged evidence showed that these populations would face more mental health risks due to the COVID-19 pandemic [38][39][40]. As such, supporting previous take-aways by Weinstein & Nguyen [3], and by Luchetti et al [35], we see evidence of no drastic increase in mental health risks in general population as an encouraging sign.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Findings on changes in well-being and psychological symptoms during the COVID-19 pandemic are accumulating from different countries, some of which found increases in distress (e.g., Elmer et al, 2020;Twenge & Joiner, 2020), whereas others did not (e.g., Fried, 2020;Weinstein & Nguyen, 2020).…”
Section: Appraisals and Change In Mental Health Symptomsmentioning
confidence: 99%